Manfaat Akupresure dan Kombinasi Madu Temulawak untuk Meningkatkan Nafsu Makan pada Balita Stunting - Dwi Agustin Pratiwi; Fauziah Hanum Nur Adriyani; Linda Yanti (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat, 2023)
Toddlers under five years old (toddlers) are the age most vulnerable to diseases caused by malnutrition. The importance of prevention and treatment efforts, both directly and indirectly, in preventing the emergence of disease due to further malnutrition. The stunting disease indicator is measured by (TB/U). Meanwhile, based on data from Banjarnegara Regency/City, the percentage of stunted toddlers is 21.23%. Factors that can be related to stunting are most likely due to a lack of appetite in toddlers so that the growth experienced by these toddlers is slower compared to healthy toddlers. To increase appetite in toddlers is by giving acupressure and ginger honey. This study used midwifery management according to Varney with the case study report method. Data collection uses primary and secondary data. Activities were carried out for 5 days. From the results of this research, carrying out acupressure care and giving ginger honey for 5 days was proven to be effective in increasing appetite in stunted toddlers.